2012
DOI: 10.11606/issn.2318-3659.v49i2p102-110
|View full text |Cite
|
Sign up to set email alerts
|

Mananoligossacarídeo em dietas para leitões desmamados

Abstract: An assay was carried out to evaluate the use of mannanoligosaccharide (MOS) in piglet diets on performance, diarrhea incidence and blood parameters. Different levels of MOS inclusion (0, 0.1 and 0.2%) for pig diets were compared. A total of 72 piglets of Topigs lineage weaned at 21 days of age with 5.28±0.90 kg of live weight were used. It was used a randomized block design to control differences between initial weights of replicates. The results show that MOS inclusion in weaning pig diets did not promote bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The effect of the use of prebiotics for growth, feed intake, and feed efficiency shows a varied response and did not influence piglet performance during the nursery period, for prebiotics such as mannooligosaccharides (CORASSA et al, 2012;SANTOS et al, 2010;SILVA et al, 2012), fructoligossacharides (VISENTINI et al, 2008), and chitooligossacharides (CHEN et al, 2009). However, with COS, some studies have reported better growth and feed efficiency in broilers (HUANG et al, 2005;LI et al, 2007) and piglets Apical villi necrosis 3 0 a 3…”
Section: Resultsmentioning
confidence: 99%
“…The effect of the use of prebiotics for growth, feed intake, and feed efficiency shows a varied response and did not influence piglet performance during the nursery period, for prebiotics such as mannooligosaccharides (CORASSA et al, 2012;SANTOS et al, 2010;SILVA et al, 2012), fructoligossacharides (VISENTINI et al, 2008), and chitooligossacharides (CHEN et al, 2009). However, with COS, some studies have reported better growth and feed efficiency in broilers (HUANG et al, 2005;LI et al, 2007) and piglets Apical villi necrosis 3 0 a 3…”
Section: Resultsmentioning
confidence: 99%
“…Regarding TP and albumin, Silva et al (2012) found values of 4.77 g/dL TP and 2.27 g/dL of albumin, Moreira et al (2014) obtained a value of 7.02 g/dL of TP and Rocha et al (2012) obtained a value of 4.14 g/dL albumin, with the range considered ideal for this protein being among 1.9-3.9 g/dL (Kaneko et al, 2008). Values below the optimal range of 6-8 g/dL (Weiss & Wardrop, 2010) were observed for TP, due to the reference values being not regional, as well as due to the nutritional management used in each specifically production system, independently from the type of packaging (insolation or EE).…”
Section: Resultsmentioning
confidence: 99%